Impact of Communicative Language Test Assessments in Enhancing Learners' Capacity - Jamiu, Lateef Adebowale (Bumi Publikasi Nusantara, 2023)
The use of communicative assessments to evaluate language learners' capacity to use the target language in real-world contexts has gained more attention and has been the subject of research in tandem with the communicative language teaching approach. Test designers should keep fundamental ideas and traits in mind when creating tests with this objective. This paper also addresses the issue of whether or not communicative test designers can provide an appropriate estimation of test takers' language skills based on the scores. Some literature reviews indicate that the use of communicative language testing may provide difficulties for test developers, and this topic is covered in the paper. Most language examinations have historically been designed to evaluate a person's language knowledge, including vocabulary and grammar. The discipline of language testing had started to concentrate on creating communicative language testing assignments by the middle of the 1980s. This indicates that the demand for communicative language exams has been acknowledged, and a lot of studies have been conducted on communicative language tests since then. By conducting this literature study, it is believed that the principles and features of communicative test design and elements other than communicative language proficiency that affect test scores and communication testing obstacles can be explored.